(untitled) (CAHIERS MAGELLANES-NS, 2024)
Financial inclusion is playing significant role for the devolvement of a country. To encourage unbanked and underbanked people to have access to banking and financial services, the government has implemented a number of financial inclusion programs over the years. The objective of this research paper is to present a thorough examination and analytical assessment of the suitability of financial inclusion initiatives in India. This research paper delves in the effectiveness and applicability flag bearer financial inclusion scheme in India. The study examines government initiative, concepts and approaches and ground level difficulties for implementation of existing schemes. In this comprehensive review of existing literature, schemes performance reports and RBI reports will identify the success and challenges of the schemes. The key performance indicators core valuation are access and reach ,usage and adoption , financial literacy.